STABILITY OF THE FLYWHEEL ENGINE IN A CARDAN SUSPENSION - Tsidylo, I.V.; Tsidylo, K.I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
A mathematical model of a flywheel engine in a cardan suspension and also its motion stability research is offered. A mechanical system with an ecologically clean energy source in the form of a flywheel in a gimbal mounted on a vibrating base is under consideration. Such a model of mechanical systems occupies, in some sense, an intermediate place between a gyroscope and a flywheel that rotates in rigidly fixed supports. Currently, we have extensive experience in researching the stability and oscillations of nonlinear systems described by nonlinear differential equations. However, the use of the mathematical theory of stability for specific problems continues to be a relevant task. The problem of stability of the proposed mechanical system is considered using the second Lyapunov method, which is applied to definitly positive functions characterizing the slow evolution of the process. The equations of motion were formulated and the influence of nonlinear terms in the equations of motion on stability was investigated. The study of the stability of the mechanical system under initial disturbances is presented, as well as the conclusions of the system movement behavior are made.